2012
DOI: 10.6026/97320630008673
|View full text |Cite
|
Sign up to set email alerts
|

In-silico comparative study of inhibitory mechanism of Plant Serine Proteinase Inhibitors

Abstract: The nematodes like root-knot and cyst are plant-parasitic pest found in horticultural and agricultural crops. They do damages in the roots of plants as a result losses million tons of production. High cost of nematicides and environment safety concern has necessitated finding of some alternative methods. Under Integrated Pest Management (IPM) such problems are solving significantly by means of target gene inhibition, agrobacterium mediated transformation etc. One of this strategy use Plant Proteinase Inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This suggests that the backbone conformation and nonbonded interactions of PfPP5 was found reasonable within a normal range. Evaluation with VERIFY 3D indicated a reasonably good sequence-to-structure agreement as in crystal structure (Prasad, Gupta, Gaponenko, & Dhar, 2012). Similar validation study was also observed by Prasad et al, (Prasad, Gupta, Gaponenko & Tiwari, 2013).…”
Section: Generation Of Pfpp5 Modelsupporting
confidence: 84%
“…This suggests that the backbone conformation and nonbonded interactions of PfPP5 was found reasonable within a normal range. Evaluation with VERIFY 3D indicated a reasonably good sequence-to-structure agreement as in crystal structure (Prasad, Gupta, Gaponenko, & Dhar, 2012). Similar validation study was also observed by Prasad et al, (Prasad, Gupta, Gaponenko & Tiwari, 2013).…”
Section: Generation Of Pfpp5 Modelsupporting
confidence: 84%
“…Refined structures of both models have gained improvement over initial models and can be seen from Ramachandran Plot statistics, ERRAT scores and VERIFY3D scores ( Table 2 ). The chosen scores have been previously used in studying mechanisms of inhibitors and functional analysis [ 43 , 44 ]. IOM-cHSP70 consists of 8 sheets, 1beta alpha beta unit, 12 beta hairpins, 10 beta bulges, 28 strands, 22 helices, 26 helix-helix interactions, 55 beta turns and 6 gamma turns while ICM-cHSP70 consist of 7 sheets, 1beta-alpha-beta unit, 11 beta hairpins, 8 beta bulges, 24 strands, 18 helices, 15 helix-helix interactions, 50 beta turns and 17 gamma turns.…”
Section: Resultsmentioning
confidence: 99%
“…Overall quality G-factor for FCR-LM and FCR-Os were found to be -0.47 and -0.50, respectively, which reveals the dihedral angle position of residues in structure (Prasad et al 2012). The validation statistics and structural features of both the structures show that there is a need for further improvement in the structure.…”
Section: Modeling and Structural Validationmentioning
confidence: 94%